Peran Media Emoji Flash Card Dalam Meningkatkan Kemampuan Berbicara Peserta Pelatihan Public Speaking for Kids Umur 7-11 Tahun Di the Jannah Jember - Lidya Watin (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe the role of emoji flashcards in enhancing the speaking skills of children aged 7–11 participating in the Public Speaking for Kids program at The Jannah Institute, Jember. The study was motivated by issues regarding children's speaking abilities, specifically in the context of bullying experiences. A qualitative descriptive approach was employed, utilizing purposive sampling to select informants and purposive area selection for the study site. The research subjects consisted of two trainers (key informants) and two parents (supporting informants). Data were collected through interviews, observation, and documentation. Data analysis followed the Miles and Huberman interactive model, comprising data collection, data reduction, data display, and conclusion drawing/verification. Data validity was ensured through prolonged engagement, persistent observation, and triangulation. The analysis revealed that emoji flashcards played a positive role in stimulating improvements in children's speaking skills through the stages of selecting, organizing, and integrating images. The use of simple emoji images representing basic emotions helped children grasp visual meanings more easily this enabled them to arrange images into coherent storylines and connect visual information with their own experiences. The impact of the emoji flashcards was evident in improvements across several speaking aspects pronunciation, intonation, fluency, expression, and content accuracy. The children were able to articulate words more clearly, use varied intonation, tell stories more coherently, display appropriate expressions, and convey content relevant to the topic. In conclusion, this medium supports the development of both verbal and non-verbal communication skills in children. Therefore, emoji flashcards serve as an effective alternative learning tool for enhancing children's speaking abilities
Validasi dan Finalisasi Ratna 20 Juli 2026
Keywords: Pelatihan; Media Emoji Flash Card; Kemampuan Berbicara; Public Speaking